2015
DOI: 10.1007/978-94-017-9744-3
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Impact Assessment

Abstract: Aims and ScopeLife Cycle Assessment (LCA) has become the recognized instrument to assess the ecological burdens and human health impacts connected with the complete life cycle (creation, use, end-of-life) of products, processes and activities, enabling the assessor to model the entire system from which products are derived or in which processes and activities operate. Due to the steady, world-wide growth of the field of LCA, the wealth of information produced in journals, reports, books and electronic media ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(18 citation statements)
references
References 198 publications
(290 reference statements)
0
17
0
1
Order By: Relevance
“…factors representing the amount of damage per unit of resource use or emission, aswhere DF x,p is the damage footprint for category x (human health or biodiversity) and product p , I i,p is the amount of resource use or emission i associated with product p , and CF i , x is the characterization factor for resource use or emission i and damage category x (damage to human health or biodiversity). 34 We calculated human health damage as disability-adjusted life years (DALYs; yr) induced by climate change, stratospheric ozone depletion, toxicant exposure, photochemical ozone formation, particulate matter formation, water stress, and ionizing radiation. 32 Biodiversity loss was calculated as the time-integrated local species loss (species · yr) due to climate change, terrestrial acidification, photochemical ozone formation, freshwater eutrophication, terrestrial ecotoxicity, freshwater ecotoxicity, marine ecotoxicity, water stress, agricultural land occupation, and urban land occupation.…”
Section: Methodsmentioning
confidence: 99%
“…factors representing the amount of damage per unit of resource use or emission, aswhere DF x,p is the damage footprint for category x (human health or biodiversity) and product p , I i,p is the amount of resource use or emission i associated with product p , and CF i , x is the characterization factor for resource use or emission i and damage category x (damage to human health or biodiversity). 34 We calculated human health damage as disability-adjusted life years (DALYs; yr) induced by climate change, stratospheric ozone depletion, toxicant exposure, photochemical ozone formation, particulate matter formation, water stress, and ionizing radiation. 32 Biodiversity loss was calculated as the time-integrated local species loss (species · yr) due to climate change, terrestrial acidification, photochemical ozone formation, freshwater eutrophication, terrestrial ecotoxicity, freshwater ecotoxicity, marine ecotoxicity, water stress, agricultural land occupation, and urban land occupation.…”
Section: Methodsmentioning
confidence: 99%
“…AoP. Worth of mention here is the fact that, to the knowledge of the authors, there is no available and recommended method for endpoint modelling of a marine eutrophication indicator (Hauschild et al, 2013;Henderson, 2015), as also noted by the International Reference Life Cycle Data System (ILCD) (EC-JRC, 2010).…”
Section: Spatially Explicit Absolute Metric Of Damage To Ecosystemsmentioning
confidence: 99%
“…This fact is reflected in widespread LCIA methods, like ReCiPe (Goedkoop et al, 2012), EDIP 2003 (Hauschild and Potting, 2005), IMPACT 2002+ (Jolliet et al, 2003), and CML 2002 (Guinée et al, 2002). Recent reviews of the state-of-the-art and research needs regarding marine eutrophication impacts modelling revealed the lack of a consistent link between existing midpoints and damage level (Hauschild et al, 2013;Henderson, 2015). While the midpoint indicator models nutrients fate in the environment, the endpoint indicator further requires exposure and effects modelling for consistency with the generic LCIA framework (Udo de Haes et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The PB was compared with "Photochemical ozone formation" because both include emissions of aerosols to the atmosphere. However, the area of concern for the two indicators differ slightly, where "Photochemical ozone formation" is about ground level ozone formation (and concentration) and how this affects humans and ecosystems (EC-JRC 2010b; Hauschild and Huijbregts 2015;van Zelm et al 2016), while "Atmospheric aerosol loading" is about aerosols in the atmosphere and how the increased loading may lead to undesired effects due to changes in solar radiation and regional oceanatmosphere circulation (Steffen et al 2015). Hence, the two impact categories differ in their area of concern; however, they have been compared in this study due to their similarities in impact pathway and to allow a comparison of results for aerosols between PB-LCIA and ILCD-LCIA.…”
Section: Photochemical Ozone Formation Atmospheric Aerosol Loadingmentioning
confidence: 99%